Editorial - Vosloo, Robert (Stellenbosch Theological Journal, 2021)
The Stellenbosch Theological Journal (STJ) is proud to present this supplement under the title "Theology from Below: Contributions from Emerging Scholars". It contains sixteen peer-reviewed essays that were first presented in March 2019 at an exciting international theological conference for post-graduate students and early career researchers. The academic quality of these essays, published after a rigorous peer-review process, bodes well for the future of theological scholarship. A special word of thanks to Drs Khegan Delport, Marnus Havenga and Calvin Ullrich for their role as guest editors of this volume. In their guest editorial they mention that one of the contributors, Dr. Alease Brown, sadly passed away before the publication of her article. We remember and honour her contribution to theological discourse in South Africa with gratitude.